Intermediate Ancient Greek Language - Palmer, Darryl (ANU Press, 2021)
Intermediate Ancient Greek Language is a series of Lessons and Exercises intended for students who have already covered most of an introductory course in the ancient Greek language. It aims to broaden and deepen students' understanding of the main grammatical constructions of Greek. Further attention is given to grammatical forms to illustrate their functions. In the Lessons, tragedy, comedy, historiography, oratory and philosophy are sources for dramatic material. The Cases have been deliberately placed late in the series of Lessons 36 to 41; students by now will be prepared to analyse Case usage. Consideration of prepositions in Lesson 42 naturally follows the Cases. Lesson 43, on correlative clauses, links with adjectival and adverbial constructions in previous Lessons. The final Lesson 44 deals with exclamations. Throughout the book, the author relies on genuine Greek sources for the passages in the Lessons and Exercises.